2010
DOI: 10.1007/s00442-010-1833-8
|View full text |Cite
|
Sign up to set email alerts
|

Simple ecological trade-offs give rise to emergent cross-ecosystem distributions of a coral reef fish

Abstract: Ecosystems are intricately linked by the flow of organisms across their boundaries, and such connectivity can be essential to the structure and function of the linked ecosystems. For example, many coral reef fish populations are maintained by the movement of individuals from spatially segregated juvenile habitats (i.e., nurseries, such as mangroves and seagrass beds) to areas preferred by adults. It is presumed that nursery habitats provide for faster growth (higher food availability) and/or low predation risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 65 publications
0
74
0
Order By: Relevance
“…This behavior could serve as a mechanism to maximize successful settlement or recruitment to preferred habitat . It has been shown that seagrass beds have lower predation risk compared with coral reefs (Grol et al 2011, Kimirei et al 2013. Adaptive be havior that leads to successful orientation and recruitment to seagrass beds can thus ultimately lead to increased survival, which is critical for population maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior could serve as a mechanism to maximize successful settlement or recruitment to preferred habitat . It has been shown that seagrass beds have lower predation risk compared with coral reefs (Grol et al 2011, Kimirei et al 2013. Adaptive be havior that leads to successful orientation and recruitment to seagrass beds can thus ultimately lead to increased survival, which is critical for population maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…This preference for seagrass cues might reflect innate behavior that has been genetically selected for through higher survival rates of fish with this trait, and could be a similar mechanism as that of, for example, reef fish that may use chemical cues from terrestrial forest vegetation to navigate towards coastal environments (Dixson et al 2008). Preferential selection for this trait could result from higher survival chances of fish that locate and settle in seagrass habitat (Grol et al 2011) irrespective of the presence of conspecifics, compared with those that are more attracted to conspecifics irrespective of seagrass presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In understanding population dynamics it is important to study the habitat of the fish as this plays a significant role in their survival both as juveniles and as they grow into adult forms [22]. Here, a habitat is the interaction of a fish species with biotic and abiotic factors to support a healthy population [23].…”
mentioning
confidence: 99%
“…Many fish species move among different coastal habitats created by mangroves, seagrass beds, and coral reefs during their life cycles (Grol, Nagelkerken, Rypel & Layman, 2011). Consequently, conservation efforts to protect species and biodiversity are developing to provide protection of habitats including linking corridors for all life stages (Mumby et al, 2004;Sale et al, 2005).…”
mentioning
confidence: 99%